PENGARUH PENGGUNAAN E- MONEY, LITERASI KEUANGAN, DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF GENERASI Z MASYARAKAT KOTA BATAM - Devita Sari, Lola; Hikmah, Hikmah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
This study aims to determine the influence of e-money, financial literacy and lifestyle on the consumer behavior of generation Z of Batam City society. The number of respondents used from BPS (Central Statistics Agency) Batam City data is generation Z respondents. The sample used in this study was 100 people using the slovin formula. The type of this study is quantitative with multiple linear regression as an analysis tool and IBM SPSS Statistic 30 as a test tool. The results of this study indicate a positive and significant influence on the e-money and lifestyle variables and a negative and significant influence on the financial literacy variable on the consumer behavior of generation Z of Batam City society partially. In the f test, it was found that the e-money, financial literacy and lifestyle variables simultaneously influenced the consumer behavior of generation Z of Batam City society.